The return to schooling: estimates from a sample of young Australian twins - Miller, Paul; Mulvey, C.; Martin, N. (Elsevier BV * North-Holland, 2006)
This study uses a sample of young Australian twins to examine whether the findings reported in Ashenfelter and Krueger (1994) and Miller, Mulvey, and Martin (1994) are robust to choice of sample and dependent variable. The economic return to schooling in Australia is between 5 and 7 percent when account is taken of genetic and family effects using either fixed-effects models or the selection effects model of Ashenfelter and Krueger. Given the similarity of the findings in this and in related studies, it would appear that the models applied by Ashenfelter and Krueger are robust. Moreover, viewing the OLS and IV estimators as lower and upper bounds in the manner of Black, Berger and Scott (2000), it is shown that the bounds on the return to schooling in Australia are much tighter than in Ashenfelter and Krueger, and the return is bounded at a much lower level than in the US.